Leadership Strategies of Administrative Heads in Shaping a Conducive Work Climate: A Case Study of SMAN 12 Pekanbaru - Srimawati, Indah; Setyaningsih, Rini; Irawati, Irawati; Paiman, Paiman (Journal of Asian Islamic Educational Management (JAIEM), 2025)
This study aims to reveal the strategy of the head of administrative staff in creating a conducive work climate at State High School 12 Pekanbaru and to identify the supporting and inhibiting factors. A descriptive qualitative approach was used with the head of administration as the key informant and the principal and administrative staff as additional informants. Data were collected through observation, interviews, and documentation, then analyzed thematically through data reduction, data presentation, and concluding with triangulation techniques of sources, techniques, and time. The results showed that the head of administrative staff implemented open communication strategies, routine rewards, division of tasks according to competence, and strong team collaboration. Supporting factors include effective communication, appreciation of creativity, team commitment, and availability of work facilities. Inhibiting factors include limited resources, weak interpersonal communication, and lack of understanding between staff. This study concludes that participatory and communicative administrative leadership plays a significant role in creating a positive work climate. These findings provide implications for strengthening school administrative governance in the context of effective education management.